Inhibition of colonization of the chicken caecum with Salmonella typhimurium by pre-treatment with strains of Escherichia coli. - Barrow, P. A. (Cambridge University Press, 1986)
Simultaneous oral administration of broth cultures of three strains of Escherichia coli isolated from sewage and an abattoir strongly inhibited the colonization of a subsequently administered strain of Salmonella typhimurium. The three strains were protective against the S. typhimurium strain under a variety of conditions: in different breeds and in chickens fed different diets. The strains were not equally effective against other salmonella strains. Oral administration of the strains produced a statistically significant reduction in the excretion of the S. typhimurium strain over a period of 7 weeks.